Developing Picture Series in Recount Text for Eighth Grade Students of MTs Darul Huda Wlingi - Azizah, Faridah; Makrifah, Istina Atul; Saifudin, Ahmad (Universitas Nahdlatul Ulama Blitar, 2022)
This research aimed, describe the process and result of developing picture series in recount text for 8th grade students of MTs. Darul Huda Wlingi. Writing is the basic skills for students. Generally teachers teach recount text material in school based on books, students felt bored and look monotonous. Students need learning media that interesting and easy to understand. This research was conducted developing picture series media in recount text. The object is eighteen Â students of class 8th. This research method using the Dick and Carry, The researcher was made instrument need analysis questionnaire, validation questionnaire were conducted media expert, material expert, and students responds. Based on the result above obtained media expert was 82,5%, material expert wasÂ 88% and students responds was 82%. The result of media expert, material expert and student responses that developing picture series in recount text has a feasible of validity could be used.